Bibliography on Cold Regions Science and Technology, Volume XXVI, Part 2. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1972)
The report is a companion issue to CRREl Report 12, Vol. XXVI, Pt. 1. The latter contains the full bibliographic citations referred to in the author and subject indexes included in this issue. (Author) See also AD-752 083.